Epidemiology of cancer‐related weight loss and sarcopenia in the UK and Ireland: incidence, prevalence, and clinical impact. Issue 2 (8th June 2020) - Sullivan, Erin S.; Daly, Louise E.; Power, Derek G.; Ryan, Aoife M.
Abstract: Background: Weight loss (WL) and sarcopenia are associated with negative oncological outcomes including poor treatment tolerance, decreased quality of life, and reduced survival. The number of patients affected by sarcopenia and WL in Ireland and the UK is unknown. Methods: A systematic review was undertaken to determine median rate of WL > 5% and computed tomography‐diagnosed sarcopenia in oncology populations. Gaps in the literature were supplemented using local data, collected as part of a 5 year prospective study. Rates of WL and sarcopenia in the population were extrapolated from these data based on incidence and prevalence of each cancer as per national cancer registries. Results: We estimated that across Ireland and the UK, 128 892 cancer patients (34%) are affected by WL > 5% annually (121 641 UK; 7251 Ireland) and there are 133 707 annual cases of sarcopenia in cancer patients (35%) (126 265 UK; 7442 Ireland). Furthermore, we estimate that there are 716 124 and 771 589 cancer survivors with history of WL > 5% or sarcopenia, respectively. Conclusions: Large numbers of patients are affected by cancer‐related malnutrition. Given the impact of malnutrition on oncological outcomes and long‐term frailty, there is an urgent need to improve access to cancer nutrition care.